Prospek Swasembada Beras di Provinsi Nusa Tenggara Timur: Metode LQ, DLQ, dan Tipologi Klassen - Amudi Pandapotan Saragih (Jurnal Statistika Terapan (ISSN 2807-6214), 2025)
Food self-sufficiency is one of the Asta Cita programs of Indonesian President Prabowo and Indonesian Vice President Gibran Rakabuming Raka in the field of food security. The Provincial and Regional Governments in East Nusa Tenggara (NTT) are committed to supporting the implementation of the food security improvement strategy program in NTT. This study focuses on grouping rice production bases based on Regency/City in NTT using the Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Klassen Typology Quadrant Analysis methods. Based on the results of the LQ and DLQ calculations, they are then classified into the Klassen typology section to see the prospects of each Regency/City classified into 4 quadrants. Quadrant I includes the regencies of West Sumba, Ende, and Central Sumba, Quadrant II includes the regencies of TTS, TTU, Alor, Sikka, and Sabu Raijua, Quadrant III includes the regencies of East Sumba, Kupang, Ngada, Manggarai, Rote Ndao, West Manggarai, Nagekeo, East Manggarai, and Kupang City, and Quadrant IV includes the regencies of Belu, Lembata, East Flores, SBD, and Malaka.